Specialpedagogisk forskning och tidiga insatser (Stockholm University Press, 2025)
The anthology Special Education Research and Early Intervention contains twenty chapters that highlight the special education knowledge area, with an emphasis on its inclusive practices and didactic applications. The chapters in this anthology explain theoretical frameworks, analyze needs and trends, summarize research and describe empirical studies, where a common theme is what supports children's development and learning. A particular focus is on stimulating activities for younger children, and for children with disabilities, regardless of their age. Most of the forty-four contributing authors are researchers working at various higher education institutions in Sweden and the USA. Two of the international contributors are collaborators who have contributed to developing this research field in our context. Several contributions in the anthology are linked to the Graduate School of Special Education with a focus on early intervention, which is funded by the Swedish Research Council, which includes Stockholm University, Jönköping University, Linköping University and Karolinska Institutet. The special education interventions illustrated in the anthology span a broad spectrum of interventions with the aim of changing, developing abilities and preventing difficulties. The first part contains texts that provide definitions of concepts, present theories and summarise research results in a comprehensive manner. The second part of the anthology contains fifteen chapters with applied studies, sometimes with experimental design, where different programmes, tools and interventions have been tested. What these chapters have in common is that they are based on dissertation studies and other empirical studies with the aim of promoting development, learning and participation for different groups of children and pupils. The contributions show the content that early special education interventions, support and specific support can have in our context and they are examples of the growing research field of applied special education.